Pengaruh Dukungan Teman Sebaya, Kemampuan Self-Control, Dan Tingkat Keseriusan Mahasiswa Terhadap Kinerja Tugas Perkuliahan Dalam Mata Kuliah Kewirausahaan - Aji Surakhmat; Olvin Kristin (Jurnal Ekonomi, Akuntansi, dan Perpajakan, 2024)
This study aims to investigate the influence of support from peers, self-control abilities, and students' level of seriousness on the performance of lecture assignments in entrepreneurship courses. Through data collection using questionnaires and regression analysis, this research explores the relationship between these variables and student task performance. The findings from this research can provide valuable insights for curriculum managers and lecturers to improve the effectiveness of learning in entrepreneurship courses.